I believe it could be 5/6 ? I don’t know.
The general formula for the sides of right triangle is
a² + b² = c²
Subtitute the equation of a and b to the formula a² + b², evaluate if the answer will be the same as the equation of c²
a² + b²
= (m² - n²)² + (2mn)²
= (m² - n²)(m² - n²) + (2mn)(2mn)
= (m⁴ - 2m²n² + n⁴) + 4m²n²
= m⁴ + 2m²n² + n⁴
Factorize the result
m⁴ + 2m²n² + n⁴
= (m² + n²)(m² + n²)
= (m² + n²)²
= c²
It's proven by the formula that c² = (m² + n²)²
so the c will be m² + n²
The answer to the question is: y=-47
If f(x) is an inverse of g(x),
when
f(x)=y
g(y)=x
aka
f(g(x))=x
g(f(x))=x
basically, the values should be swiched
example
f(x)=
(1,2)
(2,3)
(4,5)
then g(x)=
(2,1)
(3,2)
(5,4)